Outcome of conservative and surgical treatment of enchondromas and atypical cartilaginous tumors of the long bones: retrospective analysis of 228 patients - Omlor, Georg; Lohnherr, Vera; Lange, Jessica; Gantz, Simone; Mechtersheimer, Gunhild; Merle, Christian; Raiss, Patric; Fellenberg, Jörg; Lehner, Burkhard (BMC musculoskeletal disorders, 2019)
Sufficient data on outcome of patients with clinically and radiologically aggressive enchondromas and atypical cartilaginous tumors (ACT) is lacking. We therefore analyzed both conservatively and surgically treated patients with lesions, which were not distinguishable between benign enchondroma and low-grade malignant ACT based upon clinical and radiologic appearance.
Gesehen am 23.05.2019